2009
DOI: 10.1590/s1516-89132009000100007
|View full text |Cite
|
Sign up to set email alerts
|

Effect of naringerin on biochemical parameters in the streptozotocin-induced diabetic rats

Abstract: Amongst the numerous co-adjuvant therapies which could influence the incidence and progression of diabetic complications, antioxidants and flavonoids are currently being tested in clinical trials. We investigated the effect of naringerin on biochemical parameters in streptozotocin-induced (STZ -60 mg/kg, i.p.) diabetic rats. Male rats were divided into four groups: G1: untreated controls; G2: normal rats receiving naringerin; G3: untreated diabetics; G4: diabetics rats receiving naringerin. The naringerin (50m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
5
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 43 publications
5
5
0
1
Order By: Relevance
“…Nevertheless, AST and ALT levels were significantly increased in diabetic group animals compared to the normal control group in the current study. These results were in agreement with studies conducted by Elgazar et al (2013) and Fernandes, Novelli, Fernandes, and Galhardi (2009) in which they reported that levels of AST and ALT were increased in the serum of diabetic rats. In contrary to that, there was a decrease in plasma AST and ALT levels in both BV-treated groups.…”
Section: Discussionsupporting
confidence: 94%
“…Nevertheless, AST and ALT levels were significantly increased in diabetic group animals compared to the normal control group in the current study. These results were in agreement with studies conducted by Elgazar et al (2013) and Fernandes, Novelli, Fernandes, and Galhardi (2009) in which they reported that levels of AST and ALT were increased in the serum of diabetic rats. In contrary to that, there was a decrease in plasma AST and ALT levels in both BV-treated groups.…”
Section: Discussionsupporting
confidence: 94%
“…Some flavonoids, the flavonols, flavones and catechins, found in the fruits, vegetables, whole grains and grasses, have been also used in medicine against osteoporosis and inflammation, because they inhibit the precaution of the prostaglandin, diminishing the synthesis of nitric oxid, having a very important antioxidant characteristic (Bianchi and Antunes, 1999;Novelli Filho and Novelli, 2005). Fernandes et al (2009) reported that the level of triacylglycerols, total cholesterol and LDL in the serum of the diabetic rat groups administred naringerin was lower than in the diabetic rat group, showing that the flavonoids decreased the triacyglycerols and total cholesterol in the rats blood. Diniz et al (2005b) found that fiber had also an antioxidant effect.…”
Section: Antioxidants and Preventionmentioning
confidence: 97%
“…Three days following STZ injection, a random blood glucose (RBG) was measured using glucometer (Oncall-plus, Germany) at the tail vein. Rats with RBG level of more than 16.5 mmol/ L was considered as diabetics (19). After 4 weeks of DM induction, the rats were further subdivided into 5 groups; control (Ctr) and control-treated with naringenin (Ctr-NG), non-treated diabetic (DM-Ctr), diabetic treated with metformin (DM-MTF) as positive control group and diabetic treated with naringenin (DM-NG).…”
Section: Research Frameworkmentioning
confidence: 99%